1977
DOI: 10.3758/bf03214231
|View full text |Cite
|
Sign up to set email alerts
|

Note on functional measurement and data analysis

Abstract: The guiding idea of functional measurement is that measurement theory and substantive theory form an organic unity. Psychological scales are inherent in the statement of quantitative psychological laws, and these laws themselves form the base and frame for psychological measurement. Valid scales thus depend on empirically valid laws. But establishing empirical validity of any law requires appropriate data analysis. Several statistical problems are discussed with respect to simple algebraic laws. To illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…Curtis and Rule (1977) analyzed their data in terms of a two-stage model for psychophysical judgments which has proved extremely useful in other situations (Curtis, Attneave, & Harrington, 1968;Curtis & Mullin, 1975). Blankenship and Anderson (1976) made use of the functional measurement approach (Anderson, 1977) and analyzed their data in terms of a weighted sum integration model. This paper is concerned with the analysis and interpretation of ratio-setting data.…”
mentioning
confidence: 99%
“…Curtis and Rule (1977) analyzed their data in terms of a two-stage model for psychophysical judgments which has proved extremely useful in other situations (Curtis, Attneave, & Harrington, 1968;Curtis & Mullin, 1975). Blankenship and Anderson (1976) made use of the functional measurement approach (Anderson, 1977) and analyzed their data in terms of a weighted sum integration model. This paper is concerned with the analysis and interpretation of ratio-setting data.…”
mentioning
confidence: 99%
“…Birnbaum and Veit concluded that if difference judgments are represented either by a subtractive or ratio model, the additive or parallel-averaging models must be rejected for the size-weight illusion. Anderson's (1977Anderson's ( , 1981Anderson's ( , 1983 reviews of this topic reached conclusions (based on scale-dependent research) different from those of Birnbaum and Veit (1974), although he did not cite their study. Thus, despite a similarity of purpose and terminology, Anderson's (1983) two-operation logic should not be confused with the scalefree test as used by Birnbaum (1974) and by Birnbaum and Veit (1974).…”
Section: Scale-free Tests and Real Disagreementsmentioning
confidence: 85%
“…But these correlation-scatterplot statistics are deceiving; they seem to test the model but they do not really do so. This example is but one of many that tell the same story (Anderson, 1976a(Anderson, , 1977Anderson & Shanteau, 1977;Birnbaum, 1973).…”
Section: Need For Test Of Goodness Of Fitmentioning
confidence: 99%
“…Significant discrepancies need not require rejection of a model (Anderson, 1977), for they could reflect the approximate character of some simplifying assumption. On the other hand, they could also signal inadequacies in the basic assum ptions,…”
Section: Interpretation Of the Discrepanciesmentioning
confidence: 99%